(untitled) (Altre Modernità, 2017)
Despite ‘pendulum swings’ and ‘revolutions’ throughout the history of language teaching, the association of errors and grammar (of one’s native language or of a second/foreign language) has been a constant concern of language professionals as well as the subject of academic interest in linguistics, second language acquisition and grammaticology. Grammar books are ideally suited to the investigation of how perceptions about errors, along with associated notions such as those of grammaticality, acceptability and correctness, have changed throughout the centuries. While much academic interest has been devoted to the analysis of English pedagogical grammar books (and usage manuals) aimed at native speakers (‘prescriptive’ grammar books and usage manuals, cf. Peters 2006), very little is known about English pedagogical grammar books for non-native speakers, particularly those published in the 20th and 21st centuries. A recent development within the realm of pedagogical grammaticography has been the genre of pedagogical grammar books specifically aimed at teachers of English as a second or foreign language (Nava 2008). Grammar books such as Celce Murcia and Larsen Freeman (1999) have the express purpose of presenting English grammar drawing on research in linguistics and second language acquisition that is thought to be relevant to the practical business of teaching grammar to second/foreign language learners. In this contribution, after identifying a few key issues in the way the notion of ‘error’ has been conceived of in linguistics, second language acquisition and grammar writing, I will present a study of how a selection of pedagogical grammar books for English language teachers view and operationalize errors.